Cytochrome P450 catalyses the 29-carboxyl group formation of celastrol. (October 2021) - Zhou, Jiawei; Hu, Tianyuan; Liu, Yuan; Tu, Lichan; Song, Yadi; Lu, Yun; Zhang, Yifeng; Tong, Yuru; Zhao, Yujun; Su, Ping; Wu, Xiaoyi; Huang, Luqi; et al.
Abstract: Celastrol, a potent anticancer and anti-obesity drug, was first isolated from Tripterygium wilfordii Hook. f. and it is produced in small quantities in many members of the Celastraceae family. The heterologous reconstitution of celastrol biosynthesis could be a promising method for the efficient production of celastrol and natural and unnatural derivatives thereof, yet only part of the biosynthetic pathway is known. Here, we report a cytochrome P450 monooxygenase ( TwCYP712K1 ) from T. wilfordii that performs the three-step oxidation of friedelin to polpunonic acid in the celastrol pathway. Heterologous expression of TwCYP712K1 showed that TwCYP712K1 catalyses not only the transformation of friedelin to polpunonic acid but also the oxidation of β -amyrin or α -amyrin. The role of TwCYP712K1 in the biosynthesis of celastrol was further revealed via RNA interference. Some key residues of TwCYP712K1 were also screened by molecular docking and site-directed mutagenesis. Our results lay a solid foundation for further elucidating the biosynthesis of celastrol and related triterpenoids. Graphical abstract: Image 1 Highlights: Several cytochrome P450 monooxygenase was mined from T. wilfordii . The role of TwCYP712K1 in celastrol biosynthesis was revealed. The catalyst performance of TwCYP712K1 was improved by site-directed mutagenesis. New function of MtCYP72A63 was found.